MARKET POWER AND EFFICIENCY IN INDIGENOUS SMALL RUMINANT MARKETING CHANNELS IN MARSABIT, KENYA - Juma, G. P.; Drucker, A. G.; Baltenweck, I.; Ngigi, M. (ILRI and Egerton University, 2006)
Eighty percent of Kenya’s land is arid and semi arid (ASAL). The ASALs are best suited for indigenous livestock production, particularly small ruminants. They offer employment to a majority of people in the areas, and thus contribute to general livelihoods. The “livestock revolution” is projected to double meat consumptions in the developing countries, by the year 2020 compared to 1993. The rural poor are expected to benefit from this growing market, yet pastoral population in arid districts of Kenya lack reliable marketing outlet which would provide increased benefits from indigenous small ruminant resource to both pastoralists and consumers in the ASAL region and beyond. One contributing limitation is lack of data and information on the marketing of indigenous small ruminants, subsequently leading to gaps in the existing knowledge; and a failure to appreciate the importance of indigenous animals. The need for data and information on marketing associated with the development of small ruminant’s resources creates a demand for research to provide such information. This paper aims at contributing to filling this information gap by collecting and analyzing data on the marketing of indigenous small ruminants. The paper in particular examines the existing market channels, quantifies market costs and margins, and assesses opportunities for producers to access markets. A crosssectional survey of 148 traders involved in the selling and/or buying of indigenous small ruminants was conducted in Marsabit district and the city of Nairobi. In Marsabit the survey was carried out in local markets which act as collection points close to the producer, while Nairobi serves as the terminal market and the last collection point. A simple random selection was done in the markets to select traders. The structure, conduct and performance approach was used in analyse of market channels. Results reveal two market channels through which indigenous small ruminants flow from the producer to the terminal market. A Lorenz curve and Gini coefficient (G) results of both primary traders and secondary traders showed highly concentrated markets